Derivation and Validation of a Prognostic Scoring Model Based on Clinical and Pathological Features for Risk Stratification in Oral Squamous Cell Carcinoma Patients: A Retrospective Multicenter Study - Zhou, Jiaying; Li, Huan; Cheng, Bin; Cao, Ruoyan; Zou, Fengyuan; Yang, Dong; Liu, Xiang; Song, Ming; Wu, Tong (Frontiers in Oncology, 2021)
Objective: To develop and validate a simple-to-use prognostic scoring model based on clinical and pathological features which can predict overall survival (OS) of patients with oral squamous cell carcinoma (OSCC) and facilitate personalized treatment planning. Materials and Methods: OSCC patients (n = 404) from a public hospital were divided into a training cohort (n = 282) and an internal validation cohort (n = 122). A total of 12 clinical and pathological features were included in Kaplan-Meier analysis to identify the factors associated with OS. Multivariable Cox proportional hazards regression analysis was performed to further identify important variables and establish prognostic models. Nomogram was generated to predict the individual’s 1-, 3‑ and 5‑year OS rates. The performance of the prognostic scoring model was compared with that of the pathological one and the AJCC TNM staging system by the receiver operating characteristic curve (ROC), concordance index (C-index), calibration curve, and decision curve analysis (DCA). Patients were classified into high- and low-risk groups according to the risk scores of the nomogram. The nomogram-illustrated model was independently tested in an external validation cohort of 95 patients. Results: Four significant variables (physical examination-tumor size, imaging examination-tumor size, pathological nodal involvement stage, and histologic grade) were included into the nomogram-illustrated model (clinical-pathological model). The area under the ROC curve (AUC) of the clinical-pathological model was 0.687, 0.719 and 0.722 for 1-, 3- and 5-year survival, respectively, which was superior to that of the pathological model (AUC=0.649, 0.707, 0.717, respectively) and AJCC TNM staging system (AUC=0.628, 0.668, 0.677, respectively). The clinical-pathological model exhibited improved discriminative power compared with pathological model and AJCC TNM staging system (C-index=0.755, 0.702, 0.642, respectively) in the external validation cohort. The calibration curves and DCA also displayed excellent predictive performances. Conclusion: This clinical and pathological feature based prognostic scoring model showed better predictive ability compared with the pathological one, which would be a useful tool of personalized accurate risk stratification and precision therapy planning for OSCC patients.